2021
DOI: 10.7717/peerj.10702
|View full text |Cite
|
Sign up to set email alerts
|

Improved salt tolerance of Chenopodium quinoa Willd. contributed by Pseudomonas sp. strain M30-35

Abstract: Background Plant-growth-promoting rhizobacteria (PGPR) can promote plant growth and enhance plant tolerance to salt stress. Pseudomonas sp. strain M30-35 might confer abiotic stress tolerance to its host plants. We evaluated the effects of M30-35 inoculation on the growth and metabolite accumulation of Chenopodium quinoa Willd. during salt stress growth conditions. Methods The effects of M30-35 on the growth of C. quinoa seedlings were test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Salinity is a major threat to agricultural productivity. It inhibits the growth and development of plants by affecting many physiological, biochemical, and metabolic processes ( 2 ). Salinity may cause nutrient deficiencies or imbalances via the competition of Na + and Cl − with nutrients such as K + , Ca 2+ , and NO − ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinity is a major threat to agricultural productivity. It inhibits the growth and development of plants by affecting many physiological, biochemical, and metabolic processes ( 2 ). Salinity may cause nutrient deficiencies or imbalances via the competition of Na + and Cl − with nutrients such as K + , Ca 2+ , and NO − ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…PGPRs are known to promote plant growth through the production of indole-3-acetic acid (IAA), siderophores, hydrogen cyanate and nitrogenase, and phosphate solubilization. They also possess heavy metal detoxifying activity, enhance salinity tolerance, and are effective in the biological control of plant pathogens, and so forth ( 2 , 4 6 ). The genus Bacillus comprises typical species of PGPRs that are applied as biofertilizers and competitors of plant pathogens to enhance plant growth, for example, by promoting seedling emergence, enhancing plant biomass, and controlling disease ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, biological methods commonly worked on lighter level saline-alkali soil, such as Chenopodium quinoa . As a halophyte, Chenopodium quinoa grows well and improves soil properties under moderate salt stress (100–200 mM of NaCl) [ 22 ]. However, the survival rate is low under high saline-alkali stress.…”
Section: Introductionmentioning
confidence: 99%
“…These results were in agreement with previous studies that also investigated the alleviation of salt stress by Pseudomonas in plant development. Cai et al (2021) reported that Chenopodium quinoa Willd. inoculated with Pseudomonas sp.…”
Section: Evaluate the Ability To Stimulate Peanut Growth Under Salt S...mentioning
confidence: 99%